Ius Constitutum dan Ius Constituendum Pedoman Penjatuhan Hukuman: Studi Perbandingan Hukum Indonesia dan AS - Maloky, Marlen Novita (Jurnal Ragam Pengabdian, 2026)
Sentencing guidelines serve as an essential reference for judges in rendering fair, certain, and beneficial decisions. However, the criminal justice system in Indonesia still faces various problems, such as inconsistent verdicts, ultra petita decisions, and sentences that are disproportionate to the severity of the crimes committed. This occurs because the sentencing guidelines regulated under Articles 53–56 of Law Number 1 of 2023 concerning the Criminal Code (KUHP) and Supreme Court Regulation Number 1 of 2020 remain general, facultative, and non-binding in nature, thereby granting judges broad room for interpretation. This study employs a micro-comparative legal research method to compare the sentencing guideline norms between Indonesia and the United States. The findings indicate that the nomenclature of Articles 53–56 of the KUHP is more accurately classified as sentencing principles, similar to Article 46 of the German Criminal Code, rather than as technical and measurable sentencing guidelines such as the United States Sentencing Commission Guidelines Manual (USSG), which is based on a point-scoring system and overseen by an independent body (USSC). This study concludes that Indonesia needs to reconstruct its sentencing guidelines with a more rigid and measurable structure, without the need to establish a new supervisory institution, as this function can be carried out by the existing Supreme Court and Judicial Commission.